2020
DOI: 10.2533/chimia.2020.953
|View full text |Cite
|
Sign up to set email alerts
|

Bioorganometallic Technetium and Rhenium Chemistry: Fundamentals for Applications

Abstract: Due to its long half-life of 2.111×105 y, technetium, i.e. 99Tc, offers the excellent opportunity of combining fundamental and ' classical ' organometallic or coordination chemistry with all methodologies of radiochemistry. Technetium chemistry is inspired by the applications of its short-lived metastable isomer 99mTc in molecular imaging and radiopharmacy. We present in this article examples about these contexts and the impact of purely basic oriented research on practical applications. This review shows how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Native non-functionalised glucose is only a very weak ligand for transition metals, and there are no stable complexes reported with 99m Tc (Klufers and Kunte 2001 ; Bowen and Orvig 2008 ). Furthermore, 99m Tc chemistry exhibits a strong preference towards N and S atoms when forming radiolabelled compounds (Alberto et al 2020 ). Nevertheless, the imaging of glucose distribution on a TLC of the hydrophilic fraction A separated from [ 99m Tc]Tc-NanoHSA using a Sep-Pak® cartridge showed that the glucose followed the distribution of 99m Tc radioactivity in 0.9% NaCl and in 85% methanol mobile phases (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Native non-functionalised glucose is only a very weak ligand for transition metals, and there are no stable complexes reported with 99m Tc (Klufers and Kunte 2001 ; Bowen and Orvig 2008 ). Furthermore, 99m Tc chemistry exhibits a strong preference towards N and S atoms when forming radiolabelled compounds (Alberto et al 2020 ). Nevertheless, the imaging of glucose distribution on a TLC of the hydrophilic fraction A separated from [ 99m Tc]Tc-NanoHSA using a Sep-Pak® cartridge showed that the glucose followed the distribution of 99m Tc radioactivity in 0.9% NaCl and in 85% methanol mobile phases (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Although complexes of rhenium have long been overlooked for their use in anticancer therapy, recent literature shows they offer great potential as potent anticancer agents in the effort to overcome the clinical limitations observed with platinumbased drugs. 9,[27][28][29][30][31] Rhenium merits particular attention among all other transition metals because of its wide range of oxidation states ranging from −1 to +7 and coordination numbers up to 9. 16,32,33 This allows it to form structurally diverse complexes with a variety of ligands and BFCs that would not be possible with other transition metals.…”
Section: Why Radiorhenium?mentioning
confidence: 99%
“…This metastable technetium isotope has been the workhorse of nuclear medicine for decades and is used in approximately 90% of all nuclear imaging applications. 20,29,50,51 Fig. 2a provides a graphic image of how extensively studied and reported 99m Tc has been over the years in comparison to the lesser emphasised radiorhenium isotopes, while Fig.…”
Section: Why Radiorhenium?mentioning
confidence: 99%
“…The oxidation states and transition-metal core play a key role in synthesis and solubility, as well as the general and biological chemistry (Liu, 2004;Alberto et al, 2020). We have therefore grouped and described the following medically applicable PDB structures according to the Re/Tc metal core which is found in these structures.…”
Section: Medical Applicationsmentioning
confidence: 99%